Exploring Motivating and De-motivating Factors of Teacher - Oli, Nabaraj (Intellectual Journal of Academic Research, 2024)
Teacher motivation is considered as one of the important area of teacher professional development. Highly motivated teacher can teach effectively in the classroom and bring changes in the outcomes of the students' performance. This research aims to explore the motivating and de-motivating factors of teachers in school education. To fulfill it, four teachers of secondary level education were purposively selected from different four schools of Aathrai Rural Municipality of Terathum district. They were interviewed time and again until data saturation. The qualitative data obtained from in-depth interview were analyzed descriptively and thematically. The findings of the study suggest teacher's responsibility and accountability, interest and desire, support from colleague and senior, salary, professional development, academic freedom, service facility, students performance are the motivating factors. On the other hand political interference, lack of administrative support, teacher's biasness, service facilities, identity crisis are founded as the de-motivation factors. The research concluded that the concerned body should understand the importance of teacher motivation which helps to improve and promote the teaching learning activities and enhance learning efficiency and proficiency.